2013
DOI: 10.1530/eje-13-0084
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for age-specific peak cortisol responses to insulin-induced hypoglycaemia in children

Abstract: Objective: Based on adult data, a peak cortisol response R500 nmol/l to insulin-induced hypoglycaemia constitutes a normal. Age-specific reference ranges for basal morning cortisol have been developed for clinical use in the paediatric population. Such reference ranges are not clearly established for peak cortisol responses to insulin-induced hypoglycaemia despite limited data suggesting an effect of age on peak cortisol. The aims of this study were to assess factors affecting the cortisol response to insulin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Those performed have included diverse study populations, and different stimulation tests, and none studied the relations between peak cortisol and age separately for each gender. Peak cortisol levels have been shown to decrease with age and to vary by sex and pubertal status after high-dose ACTH stimulation test [25] and after ITT [15,26]. Mushtaq et al [27] reported an inverse correlation between cortisol response to the 1-μg ACTH test and age in children with short stature and normal GH levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those performed have included diverse study populations, and different stimulation tests, and none studied the relations between peak cortisol and age separately for each gender. Peak cortisol levels have been shown to decrease with age and to vary by sex and pubertal status after high-dose ACTH stimulation test [25] and after ITT [15,26]. Mushtaq et al [27] reported an inverse correlation between cortisol response to the 1-μg ACTH test and age in children with short stature and normal GH levels.…”
Section: Discussionmentioning
confidence: 99%
“…The detection limit was 27 nmol/l for cortisol. A peak cortisol >500 nmol/l was considered a normal response [15,16,17]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortisol concentrations in the early morning correlate strongly with peak cortisol concentrations in dynamic tests of adrenal function5 9 10 and have been reported to be helpful screening tests in children and young people. The sensitivity and specificity of a cortisol concentration <108 nmol/L at 9:00 for the diagnosis of adrenal insufficiency are reported to be 83% and 99%, respectively, while adrenal insufficiency is unlikely when 9:00 cortisol is >381 nmol/L 11…”
Section: Diagnostic Tests Of Adrenal Functionmentioning
confidence: 99%
“…The cortisol values' amplitude is apparently greater in the pediatric population, and this might require large-cohort studies to determine reliable cortisol reference limits and covariates in childhood [35] . For cortisol analysis, the reference intervals are often method-specific, so different degrees of interference might result in very different reference limits that are not interchangeable.…”
Section: Cortisol Reference Limitsmentioning
confidence: 99%